A preliminary Examination of Fluid inclusions in Nepheline, Sorensenite, Tugtupite and Chkallovite from the Ilímaussaq Alkaline Intrusion. - Sobolev, V. S.; Bazarova, T. Y.; Shugurova, N. A.; Bazarov, L. Sh.; Dolgov, Yu. A.; Sørensen, H. (Meddelelser om Grønland, 1970)
A preliminary examination has been undertaken of fluid inclusions in four minerals from the Ilímaussaq alkaline intrusion. The apparatus used in the study has been developed in the Institute of Geology and Geophysics of the Siberian Branch of the Academy of Sciences, Novosibirsk. Primary three-phase inclusions (liquid-gas-crystals) in nepheline from naujaite homogenize in the liquid phase at 850-1040° C. The gas phase in one analysed inclusion is dominated by CO2. Primary gas-liquid inclusions in nepheline from green lujavrite homogenize at 910-970° C in the liquid phase. These temperatures are in agreement with temperatures obtained on nephelines from Lovozero, Miask and Synnur and with data from fusion experiments on the rocks in question. Primary gas-liquid inclusions in sorensenite and tugtupite from late analcimealbite veins homogenize at 400- 460° C. The liquid phase of fluid inclusions in tugtupite contains 21 weight per cent of salts-sodium chloride is assumed to be predominant. The gas phase in one primary inclusion in tugtupite is dominated by CO2. Secondary fluid inclusions in the two minerals homogenize at 350- 100° C. The temperatures obtained are in agreement with those estimated from mineralogical evidence. A big crystal of chkalovite from an ussingite-analcime vein contains several generations of fluid inclusions. The primary liquid-gas-crystal inclusions homogenize at 860-980° C. The solid phase is dissolved at 330-360° C, two immiscible liquids appear at 700-800° C. Half of the ca. 250 fluid inclusions examined belong lo this category. The several generations of secondary inclusions which embrace liquid -gas-crystal inclusions, gas-liquid inclusions and gas inclusions homogenize in several groups between 760°C and 100° C. The liquid phase of the high temperature inclusions contains 40- 44 weight per cent NaCl. The pressure at the temperature of homogenization is es timated to be higher than 1000 atm. The gas phase is dominated by CO2 and N2+ inert gases. The unexpectedly high temperature of homogenization of the primary inclusions of the chkalovite is difficult to explain. A detailed study of this problem is in preparation.